Constitutionalizing India : an ideational project - Bidyut Chakrabarty (OUP, 2018)
"Contrary to the assumption that the 1950 Constitution of India is a verbatim reproduction of the 1935 Government of India Act, the book pursues the argument that it is an outcome of ideational battle since the beginning of institutionalized British rule in India in the mid-eighteenth century. Initiated by Edmund Burke, who while impeaching the British ruler of India, Warren Hastings, strongly argued, in a rather paternalistic fashion, for the colonizers to govern India in accordance with the enlightenment values. It was a beginning which was followed as a matter of principle by the successive British administrations in India. The influence gradually became so well-entrenched that Indian nationalists were voluntarily drawn to the values that the Enlightenment Philosophy had transmitted while administering India. It was evident in the ideas of the moderate extremist nationalists, which were also imbibed by Mahatma Gandhi and B.R. Ambedkar when they articulated their vision for an independent India."--